Management and prevention of emotional burnout among members of the armed and special forces - Liliia Semenenko; Uzef Dobrovolskyi; Stanislav Petrenko; Maria Yarmolchyk; Oleksii Ishchenko (PAGEPress Publications, 2024)
With the rise in cases of professional burnout, research on best practices and opportunities for implementing emotional burnout prevention and treatment among special services and military personnel became more relevant. The aim of this study is to determine the most efficient methods of therapy and to reveal the necessity of preventing and mitigating the symptoms of emotional burnout among special services and military personnel. Additionally, best practices and opportunities for their application by Ukrainian, Kazakh, Polish, British, American, Canadian, and South Korean specialists are highlighted. Experimentation is the main approach used in this problem's investigation. As a result, the study describes the unique aspects of the jobs performed by special services and military personnel, highlights the primary approaches to treating and preventing emotional burnout, and identifies which approaches are most successful for each group of workers based on their unique personal traits. Consequently, the study delineates the particulars and attributes of the work performed by personnel in special services and military structures, outlines the primary approaches and strategies for mitigating and averting emotional exhaustion, and indicates which of these approaches work best for these groups of workers, taking into account their unique personal traits. The introduction of emotional burnout training as a preventative intervention is supported by best practices and future possibilities.